Awareness Mentality and Strategic Behavior in Science - Ball, Rafael (Frontiers in Research Metrics and Analytics, 2021)
Acknowledgement of scientific achievements was and is essentially achieved through the citation of a publication. Increasingly, however, it is no longer just the publication itself that plays an important role, but also the degree of attention that a scientist achieves with this very publication. Thus, the importance of strategic behavior in science is progressing and an awareness mentality is spreading. In this paper, the causes and backgrounds of this development are discussed, identifying the use of reductionist, quantitative systems in science management and research funding, the loss of critical judgment and technocratic dominance, quantitative assessments used for decision making, altmetrics and the like as alternative views, the use of perception scores in reference databases and universities as well as ambitions of journals as main drivers. Besides, different forms of strategic behavior in science and the resulting consequences and impacts are being highlighted.